التحليل السيميائي واللغوي للرسائل القصيرة في الهاتف النقّال والوعي اللغوي لدى جيل الشباب = Semiotic and linguistic analysis of SMS in mobile phones and language awareness of young generations = Semiotik dan linguistik analisis SMS dalam telefon bimbit dan kesedaran bahasa generasi muda - Ali, Asem Shehadeh Saleh (IIUM Press, 2015)
نطلق هذا المقال من افتراض أنّ لغة الرسائل القصيرة في الهاتف المحمول تتضمن أشكالاً وصيغاً وتراكيب لغوية عديدة ومختلفة هي عبارة عن رموز لمعانٍ اتفق عليها شباب اليوم في الإرسال والاستقبال. ولأن هذه الرسائل القصيرة تتضمن إشارات ترميزية لمفاهيم معلومة في حياتنا الاجتماعية، فسوف نجد في مفهوم السيميولوجيا أو السيمياء عونًا مهما في شرح وبيان هذه العبارات الغامضة في تلك الرسائل، علمًا بأن هذه العبارات غير مفهومة غالبًا للجيل الذي تجاوز الأربعين من العمر، بينما هي شائعة ومفهومة بين الشباب ممن تتراوح أعمارهم ما بين 12 و27 سنة تقريبًا، وهو تحديد تقريبي يتفاوت حسب البلدان. دف هذه الدراسة إلى تحليل الرسائل القصيرة في الهاتف المحمول بين الشباب خاصةً لتوضيح معانيها والدلالات التي ترمي إليها، وذلك بتحليل نماذج من الرسائل القصيرة وتفكيك عبارا ا ومفردا ا وبيان معانيها ودلالا ا في ضوء اللغة العربية السائدة في ا تمعات العربية بشكل عام، كما تقوم الدراسة بتحديد الأخطاء النحوية والصرفية والإملائية وبيان استخدام ا The article’s hypothesis is that short messages (SMS) conveyed by mobile phones consist of many different linguistic forms, formulas and structures that constitute signs of meanings agreed upon by today’s youth both in the sending and reception of such messages. And since these short messages contain signs symbolizing meanings and concepts that are known in our social life, semiotics is of much help for us in decoding the ambiguous expressions in SMS messages. Such expressions are generally unclear for the generation above forty years of age, while they are common and understood for young people between 12 to 27 years old, this being only an approximate demarcation that varies according to countries. Likewise, the present study aims at analyzing mobile phone short messages among the youth particularly in order to their meanings and connotations in light of the Arabic language that is common in Arab societies in general. The study also identifies grammatical, morphological and typographical mistakes committed in SMS and highlights their use of colloquial Arabic.